MODELS FOR STRENGTHENING THE RELIGION AND TRADITION OF THE KOMPOLAN JAILANIAN: AN ETHNOGRAPHIC STUDY - Ruslan; Maftuhah Imam (Al'Adalah, 2023)
This research is motivated by the negative impact of the globalization era. The younger generation primarily imitates foreign cultures, sometimes negates religious teachings, and neglects local traditions. Furthermore, this ethnographic study aims to describe the existence of the Kompolan Jailanian and its model of strengthening rule and religion in East Bataal, Ganding, Sumenep, East Java. The study revealed that the Kompolan Jailanian has a historical role, goals, values/teachings, practices, and particular customs in the East Bataal community. Whereas the models of strengthening Islam and tradition are remembered (dhikr), thinking (fikr), and practice (‘amal). Likewise, the strengthening strategy is also maintained in family education.